Inconclusive evidence for associations between adverse experiences in adulthood and working memory performance - Stefan Vermeent; Anna-Lena Schubert; Meriah L. DeJoseph; Jaap J. A. Denissen; Jean-Louis van Gelder; Willem E. Frankenhuis (Royal Society Open Science)
Decades of research have shown that adversity tends to be associated with lower working memory (WM) performance. This literature has mainly focused on impairments in the capacity to hold information available in WM for further processing. However, some recent adaptation-based studies suggest that certain types of adversity can leave intact, or even enhance, the ability to rapidly update information in WM. One key challenge is that WM capacity and updating tasks tend to covary, as both types of tasks require the creation and maintenance of bindings in WM; links between mental representations of information in WM. To estimate the associations between adversity and different processes in WM, we need to isolate variance in performance related to WM capacity from variance in performance related to updating ability. In this Registered Report, participants from the Dutch Longitudinal Internet studies for the Social Sciences (LISS) panel completed three WM tasks: two complex span tasks and a task measuring both binding and updating of information. In addition, we estimated participants’ exposure to neighbourhood threat, material deprivation and unpredictability. We estimated associations between the three types of adversity and latent estimates of WM capacity and updating using structural equation modelling. We did not find consistent associations between adversity and WM capacity or updating, nor did we find evidence that the associations were practically equivalent to zero. Our results show that adversity researchers should account for overlap in WM tasks when estimating specific WM abilities.